Economic burden of gastric cancer in the first six months after diagnosis. Issue 4 (17th September 2019) - Jalilian, Habib; Doshmangir, Leila; Ajami, Soheila; Mir, Habibeh; Siraneh, Yibeltal; Hasanpoor, Edris
Abstract : Purpose: Gastric cancer is the fourth most common cancer and the leading cause of death after lung cancer in the world. Considering the economic burden of cancers and their impact on household welfare, this study aims to estimate the cost of gastric cancer in Tabriz (Northwest city of Iran) in 2017. Design/methodology/approach: This was an incidence-based cost of illness study which was conducted from the perspective of society with a bottom-up costing approach. The inclusion criteria for the study were all patients ( n  = 118) with gastric cancer at the period of the first six months after diagnosis that 102 patients participated. Data were analyzed using SPSS software version 22. Findings: The mean medical direct cost was US$3288.02, 18.19 per cent paid by the patient and 81.81 per cent paid by insurance organizations and governmental subsidies. The estimated out of pocket rate was 18.19 per cent. The mean non-medical direct cost estimated at US$377.54. The mean total direct cost was US$3665.56, 26.61 per cent paid by the patient. The mean indirect cost estimated at US$505.41 and the mean total cost was US$4170.97, 35.5 per cent which imposed on the patient. The mean total cost of gastric cancer within the first six months after diagnosis was equivalent to 0.81 GDP per capita. Originality/value: Based on the findings, gastric cancer is a highly costly disease that despite insurance coverage imposes a high economic burden on the patients and their families.